The Qur’an and Sunnah as Foundational Frameworks for Islamic Religious Education in the Modern Era - Suwoko; Idham Cholid; Arinda Shalsabila Banowati; Revalina; Zulfia Nafisa Zahra (Walidem Institute and Publishing, 2026)
Objective: This study aims to explore the role of the Qur'an and Sunnah in the context of modern Islamic education, particularly in shaping moral, spiritual, and intellectual development, while addressing the challenges posed by technological advancements, globalization, and cultural changes. Theoretical framework: The study is framed around the central role of the Qur'an and Sunnah as the primary sources of guidance in Islamic education. The framework emphasizes the integration of these foundational texts into the educational process, providing both moral and intellectual guidance for the development of attitudes, behavior, and critical thinking in modern times. Literature review: Existing literature highlights the Qur'an as the primary source of Islamic teachings, providing theological, ethical, and educational foundations. The Sunnah is viewed as the practical explanation and implementation of Qur'anic teachings. Previous studies emphasize the need for incorporating these sources into modern education to address the moral crises and cultural challenges faced by Islamic societies. Methods: The research utilizes a literature review approach, analyzing existing academic works, religious texts, and educational theories to explore how the Qur'an and Sunnah contribute to the educational process in contemporary Islamic settings. Results: The study finds that the Qur'an serves as the core source of Islamic teachings, covering theological, ethical, and educational aspects, while the Sunnah supports and elaborates on the Qur'anic teachings. In modern education, particularly in Islamic Religious Education, the integration of Qur'anic values helps shape attitudes, behaviors, and critical thinking in alignment with Islamic principles. Implications: The Qur'an and Sunnah support critical thinking, moderate perspectives, and character development in the context of modern cultural changes. Novelty: This study highlights the crucial role of the Qur'an and Sunnah in contemporary Islamic education, offering a framework for their integration to address modern challenges.